KEJADIAN PNEUMONIA BALITA DI MAUMERE FLORES NUSA TENGGARA TIMUR - Nanny Lia Dewi, Vivian; Ari Agustina, Silvia (Universitas Jenderal Achmad Yani Yogyakarta, 2016)
Background: Pneumonia is the most significant disease to cause death in children compared to any other respiratoy infections, particularly in babies and children under five years old. Objective: This study aimed to investigate several risk factors for pneumonia in children under five years old in Maumere, Flores, NTT. Methods: This sudy employed collaborative qualitative-quantitative design. Data on the occurrence of pneumonia were drawn from the medical record of TC Hillers Maumere hospital, gathering information from January to July 2015. Research also involved direct observation to residents housing and interviews with health care providers and locals. Research population was children under five with a history of pneumonia, consisted of 152 children. Data were alayzed with a univariate method. Results: The majority of respondents with pneumonia were male (53.3%), co-morbid with iron deficiency anemia (20.4%), aged under 12 months (69.1%), well-nourished (56.6%), and waiting for 1-3 days at home before going to the hospital (47.5%). Direct observation suggested that Maumere was a dry and dusty area. The majority of housing roof was zinc, with topsoil floor, house ventilation were not properly adjusted, houses were over-populated, and residents still used wood and gasoline to cook. Residents had strong belief on supernatural powers. Conclusion: Risk factors that increased the occurrence of pneumonia in children under five in Maumere were age, sex, nutritional status, and environment characteristics. Keywords: Pneumonia, anemia, nutrition, housing, children